The Gender Pay Gap at the Early Stages of Academic Careers - Iga Magda; Jacek Bieliński; Marzena Feldy; Anna Knapińska (Institute of Labor Economics (IZA), 2024)
The number of countries that have devoted time and attention to establishing gender equality regulations in academia is increasing. However, various studies indicate that women remain underrepresented among tenured faculty and in senior positions, and that female academic staff earn less than male ones. The reasons for these gaps, in particular those specific to academia, remain unclear. This article analyzes Polish female and male PhD graduates to measure the pay gap between them and its progression over time. The article studies the sources of the pay gap, with a special focus on parenthood. It draws on a dataset that covers the entire population of PhD holders who were awarded their degrees and were hired at any Polish university between 2014 and 2018. The study's results reveal that despite equal pay regulations, a relatively narrow (3–5%) but stable adjusted gender pay gap already exists among early-career academics who do not have children, and that the gap widens considerably when income from outside academia (6–11%) is considered. Basic incomes of mothers in academia are 18–20% lower than those of nonmothers. A substantial fatherhood wage premium (33–37%) arises when all sources of income are considered. Academia is not necessarily an equal workplace.
Keywords: J13; J16; 330; gender pay gap; women in academia; earnings; careers